Anti-amyloidogenic Activity of IgGs Contained in Normal Plasma - O’Nuallain, Brian (Springer US, 2010)
INTRODUCTION: We have previously shown that a subpopulation of naturally occurring human IgGs has therapeutic potential for the amyloid-associated disorders. These molecules cross-react with conformational epitopes on amyloidogenic assemblies, including amyloid beta (Aβ) protein fibrils that are a pathological hallmark of Alzheimer’s disease. MATERIALS AND METHODS: Using our europium-linked immunosorbant assay, we established that ∼95% of 260 screened donor plasma samples had amyloid fibril-reactive IgGs and Aβ conformer-reactive IgGs with minimal binding to Aβ monomers. Anti-amyloidogenic reactivity was diverse and attributed to Aβ targeting multiple fibril-related binding sites and/or variations in multidentate binding. RESULTS AND DISCUSSION: There was no correlation between anti-fibril and anti-oligomer reactivity and donor age (19 to 60 years old) or gender. These findings demonstrate the inherent but diverse anti-amyloidogenic activity of natural IgGs contained in normal plasma. CONCLUSION: Our studies provide support for investigating the clinical significance and physiological function of this novel class of antibodies.